Measuring more than just economic growth to improve well-being - Danielli,S; Donnelly,P; Coffey,T; Horn,S; Ashrafian,H; Darzi,A (Journal of Public Health, 2022)
It's official: The UK is in a recession. The economy has suffered its biggest slump on record with a drop in gross domestic product (GDP) of 20.4%. 1 This is going to have a significant impact on our health and well-being. It risks creating a spiralling decay as we know good health is not only a consequence, but also a condition for sustained and sustainable economic development. 2 In this way, the health of a nation creates a virtuous circle of improved health and improved economic prosperity. How we measure prosperity is therefore important and needs to be considered.